Synthesis of silver nanoparticles in surfactant-free light-cured methacrylate resins - Asmussen, Silvana Valeria (2014)
The present study describes a simple method for preparing stable, highly dispersed spherical silver nanoparticles (Ag NPs) in surfactant-free methacrylate resins. Colloidal dispersions of silver in methacrylate resins were obtained by in situ reduction of silver nitrate. The reducing agents were hydroquinone (HQ), hydroquinone methyl ether (MEHQ) and 2,6-di-tert-butyl-para-cresol (BHT), which are added to the resins to prevent premature polymerization. The obtained finely dispersed Ag NPs, that were 5–10 nm in diameter, were maintained in a stable colloidal state for more than nine months at ambient temperature. UV–vis and TEM analysis revealed that the particle size did not change with the reaction time. Moreover, UV–vis spectra and TEM micrographs of samples stored for 9 months, showed no drastic change in average particle size. From these studies, it is concluded that the methacrylate resins used as reactive solvent act as efficient particle stabilizers preventing particle coalescence and thereby enabling long term stability. The dispersions Ag NPs/methacrylate resins were photoactivated with 0.5 wt% of 2,2-dimethoxy-2-phenylacetophenone and were photo polymerized with a UV light source of irradiance centred at 365 nm. The effective utilization of the surfaces of the formed metal nanoparticles is an advantage associated with nanoparticles formed via a surfactant-free synthesis method. The proposed process offers the possibility to use these synthesized materials for the production of colour filters for optical devices and biomaterials with improved antimicrobial properties.